Anatomical location, sex, and age modulate adipocyte progenitor populations in perivascular adipose tissues - Rendon, C. Javier; Sempere, Lorenzo; Lauver, Adam; Watts, Stephanie W.; Contreras, G. Andres (Frontiers in Physiology, 2024)
Perivascular adipose tissue (PVAT) regulates vascular function due to its capacity to synthesize vasoactive products and its mechanical properties. PVATs most abundant cells are adipocytes, and their populations are maintained by the maturation of adipocyte progenitor cells (APC), which may play a pivotal role in the pathogenesis of cardiovascular diseases. However, the distribution of APC within PVAT depots, their potential variation in spatial location, and the influence of sex and age on their abundance remain unknown. We hypothesize that APC abundance in PVAT is affected by location, age, sex and that APC subtypes have specific spatial distributions. PVAT from thoracic and abdominal aorta, and mesenteric arteries, and AT from interscapular, gonadal, and subcutaneous depots from 13-week and 30-week-old females and males Pdgfrα-CreERT2 x LSL-tdTomato mice (n = 28) were analyzed. Abdominal aorta PVAT had fewer progenitors than mesenteric PVAT and gonadal AT. Aging reduced the abundance of APC in the thoracic aorta but increased their numbers in mesenteric PVAT. Females had more APC than males in mesenteric PVAT and gonadal AT depots. APC exhibited unique spatial distribution in the aorta and mesenteric PVAT where they localized neighboring vasa vasorum and arteries. APC subtypes (APC1, APC2, APC3, diff APC) were identified in all PVAT depots. Thoracic aorta PVAT APC3 were located in the adventitia while diff APC were in the parenchyma. This study identified variability in APC populations based on depot, age, and sex. The distinctive spatial distribution and the presence of diverse APC subtypes suggest that they may contribute differently to cardiovascular diseases-induced PVAT remodeling.